2006
DOI: 10.1128/ec.00221-06
|View full text |Cite
|
Sign up to set email alerts
|

RacG Regulates Morphology, Phagocytosis, and Chemotaxis

Abstract: RacG is an unusual member of the complex family of Rho GTPases in Dictyostelium. We have generated a knockout (KO) strain, as well as strains that overexpress wild-type (WT), constitutively active (V12), or dominant negative (N17) RacG. The protein is targeted to the plasma membrane, apparently in a nucleotidedependent manner, and induces the formation of abundant actin-driven filopods. RacG is enriched at the rim of the progressing phagocytic cup, and overexpression of RacG-WT or RacG-V12 induced an increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…Biological roles of some Dictyostelium Rho GTPases have been assessed by genetic knockout and overexpression experiments, as well as localization studies, and a number of their effectors have been identified . RacE, for instance, plays a role in the regulation of cytokinesis (Larochelle et al, 1997), RacB is involved in the control of directional sensing (Park et al, 2004), whereas RacG is important for cell shape, motility and phagocytosis (Somesh et al, 2006). However, direct evidence for the sites of activity and dynamics of RhoGTPases in Dictyostelium has been lacking so far.…”
Section: Discussionmentioning
confidence: 99%
“…Biological roles of some Dictyostelium Rho GTPases have been assessed by genetic knockout and overexpression experiments, as well as localization studies, and a number of their effectors have been identified . RacE, for instance, plays a role in the regulation of cytokinesis (Larochelle et al, 1997), RacB is involved in the control of directional sensing (Park et al, 2004), whereas RacG is important for cell shape, motility and phagocytosis (Somesh et al, 2006). However, direct evidence for the sites of activity and dynamics of RhoGTPases in Dictyostelium has been lacking so far.…”
Section: Discussionmentioning
confidence: 99%
“…Of the more characterized Rac-related GTPases, several are linked to chemotaxis-related functions. Rac1A controls filopodia formation and cell motility (Dumontier et al, 2000); RacB regulates actin polymerization and chemotaxis, and is controlled by the PI3K pathway (Park et al, 2004); RacC stimulates WASPdependent F-actin assembly, and is required for PI3K activation and proper chemotaxis (Han et al, 2006); and RacG induces filopodia formation and actin polymerization, and regulates chemotaxis (Somesh et al, 2006). It is of interest to check whether Costars function depends on any of these D. discoideum Rac-related GTPases.…”
Section: Discussionmentioning
confidence: 99%
“…Cdc42-subfamily members such as Wrch1 (Aspenstrom et al, 2004, Ruusala andAspenstrom, 2008), or RhoD and Rif (Ellis andMellor, 2000, Pellegrin andMellor, 2005). In Dictyostelium, filopodia can be induced by at least four GTPases, Rac1A, B, C, and G (Dumontier et al, 2000, Somesh et al, 2006, but not all Rac GTPases expressed in this organism have been thoroughly examined. Clearly, future efforts to improve our knowledge on the commonalities and specificities of signalling pathways driving filopodia formation will have to include attempts to abolish these structures by interference with multiple GTPases simultaneously.…”
Section: Rho-gtpasesmentioning
confidence: 99%